Glucocorticoids Significantly Influence the Transcriptome of Bone Microvascular Endothelial Cells of Human Femoral Head - Qing-Sheng Yu; Wan-Shou Guo; Li-Ming Cheng; Yu-Feng Lu; Jian-Ying Shen; Ping Li (Chinese Medical Journal, 2015)
Background: Appropriate expression and regulation of the transcriptome, which mainly comprise of mRNAs and lncRNAs, are important for all biological and cellular processes including the physiological activities of bone microvascular endothelial cells (BMECs). Through an intricate intracellular signaling systems, the transcriptome regulates the pharmacological response of the cells. Although studies have elucidated the impact of glucocorticoids (GCs) cell-specific gene expression signatures, it remains necessary to comprehensively characterize the impact of lncRNAs to transcriptional changes. Methods: BMECs were divided into two groups. One was treated with GCs and the other left untreated as a paired control. Differential expression was analyzed with GeneSpring software V12.0 (Agilent, Santa Clara, CA, USA) and hierarchical clustering was conducted using Cluster 3.0 software. The Gene Ontology (GO) analysis was performed with Molecular Annotation System provided by CapitalBio Corporation. Results: Our results highlight the involvement of genes implicated in development, differentiation and apoptosis following GC stimulation. Elucidation of differential gene expression emphasizes the importance of regulatory gene networks induced by GCs. We identified 73 up-regulated and 166 down-regulated long noncoding RNAs, the expression of 107 of which significantly correlated with 172 mRNAs induced by hydrocortisone. Conclusions: Transcriptome analysis of BMECs from human samples was performed to identify specific gene networks induced by GCs. Our results identified complex RNA crosstalk underlying the pathogenesis of steroid-induced necrosis of femoral head.